2010
DOI: 10.1155/2010/461538
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Algorithms for Multistatic Sonar Systems

Abstract: Activated reconnaissance systems based on target illumination are of high importance for surveillance tasks where targets are nonemitting. Multistatic configurations, where multiple illuminators and multiple receivers are located separately, are of particular interest. The fusion of measurements is a prerequisite for extracting and maintaining target tracks. The inherent ambiguity of the data makes the use of adequate algorithms, such as multiple hypothesis tracking, inevitable. For their design, the understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…As for N n , it denotes the n-dimensional Gaussian distribution. Observe that the above assumptions are quite reasonable because of several sources of error that affect the target-originated contact parameters [14]. For example, the TDOA suffers from insufficient synchronisation between sources and receivers, distance calculations suffer from insufficient knowledge of the sound speeds and accordingly sound paths.…”
Section: System Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for N n , it denotes the n-dimensional Gaussian distribution. Observe that the above assumptions are quite reasonable because of several sources of error that affect the target-originated contact parameters [14]. For example, the TDOA suffers from insufficient synchronisation between sources and receivers, distance calculations suffer from insufficient knowledge of the sound speeds and accordingly sound paths.…”
Section: System Descriptionmentioning
confidence: 99%
“…As for the noisy measurements, the standard deviations of target-originated measurements are set as follows These values are in the similar range of values extracted from real measurements [14] and they are also commonly used in the multistatic tracking community [21]. On the other hand, for each couple source-receiver the false contacts are distributed uniformly in the smallest bistatic ellipse that contains the surveillance region.…”
Section: Performance Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As written in step 2) and 4) tracking is a major part of the multistatic software: In fact, previous research has shown that tracking algorithms like multi-hypotheses tracking (MHT) not only provide a very elegant framework to perform this task, but that, even more, the "integration of information" over time is necessary to actually do the association, i.e. kinematic information is necessary to associate contacts in the stochastically fluctuating sonar pictures [11].…”
Section: Multistatic Data Fusion Architectmentioning
confidence: 99%
“…The quality of each virtSB can be calculated in the same manner as for the sensor model in a multistatic tracker [4]. In [11], measurement uncertainties and the detection performance are appropriately modeled.…”
Section: G Virtsbs With Weightsmentioning
confidence: 99%